Use of sugarcane trash for solid biofuel production: physicochemical characterization and influence of storage time - Nakashima, Gabriela Tami (Universidade Federal de São Carlos, 2016)
In the sugarcane plantation it was common to use fire to facilitate the cutting and harvesting of sugarcane. However, Law 11,241 / 02 in São Paulo State provides the gradual elimination of this straw burning of sugarcane. The largest producer of sugarcane in Brazil is the São Paulo State, which has about 4.7 million hectares of planted area. It is estimated that one hectare produces about 14 tons of trash. Therefore, the mills have been trying to incorporate this trash in burning with the bagasse for power generation. However, high concentrations of mineral impurities are impossible its use for energy purposes. The aim of the study was to investigate the influence of storage time and particle size in the physicochemical characterization of the sugarcane trash. It was used the sugarcane trash inside and outside of the bale collected at different storage time (0, 1 and 2 years). The collected material was separated into four different particle sizes (> 0.420mm, 0.250-0.420mm, < 0.250mm and mix). The analyzes involved particle size distribution, proximate analysis, the high heating value (HHV), the chemical analysis of the components of the ashes, the images in the Scanning Electron Microscope (SEM), the Klason lignin content, the holocellulose content and extractives. There were variations in the results of the ash content with different particle sizes. It was observed a higher concentration of mineral impurities in smaller particles (< 0.250mm). The HHV varied from 15.9 to 18.3 MJ.kg-1 and showed no statistical difference for the treatments. The results indicate that the sugarcane trash presents problems related to mineral impurities which constrain its use as a solid fuel in the industry. The particle size interferes in their physicochemical characteristics. The trash can be stored in field and the time storage did not affect the quality for use as solid biofuel.
Uso do palhiço da cana-de-açúcar para a produção de biocombustíveis sólidos: caracterização físico-química e influência do tempo de estocagem
Keywords: Briquetes (Combustível); Cana-de-açúcar; Biocombustíveis; Mineral impurities; Briquettes; Particle size; High heating value; Biomass energy; Sugarcane; Briquets (fuel); OUTROS